2011
DOI: 10.3109/10715762.2011.567984
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces neurite degeneration: Prevention by tocotrienols

Abstract: Reactive oxygen species (ROS) may attack several types of tissues and chronic exposure to ROS may attenuate various biological functions and increase the risk of several types of serious disorders. It is known that treatments with ROS attack neurons and induce cell death. However, the mechanisms of neuronal change by ROS prior to induction of cell death are not yet understood. Here, it was found that treatment of neurons with low concentrations of hydrogen peroxide induced neurite injury, but not cell death. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 42 publications
4
45
0
Order By: Relevance
“…These results indicate that axonal beading occurs in hippocampal neurons of vitamin E-deficient and normal old mice, extending our previous findings from cultured models (16,17). It is possible that axonal degeneration relates to changes in the CRMP-2 expression.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results indicate that axonal beading occurs in hippocampal neurons of vitamin E-deficient and normal old mice, extending our previous findings from cultured models (16,17). It is possible that axonal degeneration relates to changes in the CRMP-2 expression.…”
Section: Discussionsupporting
confidence: 77%
“…Urano et al reported that a large number of synaptic vesicles had accumulated in synapses of aged rats and young rats exposed to reactive oxygen species (15). Previously, we reported that treatment of cerebellar granule neurons with a low concentration of hydrogen peroxide induced axon and dendrite degeneration, but not cell death (16,17). However, these data were from cultured models, and axonal condition in living tissues…”
mentioning
confidence: 46%
“…In recent years, evidence has accumulated for a role of reactive oxygen metabolites as a mediator of tissue injury in several animal models (Özdemir et al 2010;Fukui et al 2011;Sato et al 2011). Although the exact mechanisms of free-radical generation are still not completely understood, it is postulated that the antioxidant glutathione (GSH) depletion by the intestinal parasites may be a trigger for the production of reactive oxygen species (ROS) (Cam et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus by modulating ROS, LIF could also influence differentiation. Given the reduction of ROS in LIF þ cultures, it was important to address whether the observed neuroprotective effect extends to ROS induced by extrinsic factors as may be encountered in a hostile niche upon transplantation or in disease [58][59][60][61]. H 2 O 2 is often generated in cells in response to a hostile environment and has widely been used to induce ROS in a variety of neuronal cells [60,61].…”
Section: Reduced Apoptosis Correlated To Reduction In Caspases and Rosmentioning
confidence: 99%